Relative abundance, diversity and activity patterns in the medium and large land mammals in Pájaro Sombrilla trail, Alberto Manuel Brenes Biological Reserve, Alajuela, Costa Rica - Sánchez Porras, Ronald (2021)
The use of trap cameras allow us to recorded and analyzed the populations of medium and large terrestrial mammals present in the Pajaro Sombrilla trail in Alberto Manuel Brenes Biological Reserve, Alajuela, Costa Rica. The research was from August 2017 to September 2018, and covered the dry and rainy seasons. With a sampling effort of 1584 trap days, 21 species of mammals belonging to 7 orders and 15 families were captured. Ten species of carnivores were registered, this was the most represented order. The study showed a specific richness of S = 21. The Margalef index obtained a high diversity (dry Dmg = 2.47, rainy Dmg = 3.09), in addition the Pielou index indicated that in both seasons abundance was maintained from medium to high (dry e = 0.69, rainy e = 0.69). The Shannon-Wiener index showed a moderate diversity (H´ = 2.04; dry H´ = 1.86, rainy H´ = 2.03). The Hutchenson test showed that the Shannon-Wiener index is significant, so the rainy season differs from the dry season (t = 1.69; p = 0.05; gl = 619). 95.45% of the terrestrial species of medium and large mammals were captured on the Pajaro Sombrilla trail, according to the results of the species accumulation curve. In relation to the calculated relative abundance index, the most abundant species were Pecari tajacu (IAR = 18.50), Leopardus pardalis (IAR = 2.21), Puma concolor (IAR = 2.15) and the Didelphidae family (IAR = 2.78). Concerning to activity patterns, P. tajacu presented daytime activity (6: 00-20: 00). L. pardalis had catameral activity with two maximum peaks (6: 00-8: 00 and the other from 22:00 - 24:00), P. concolor presented catameral activity with maximum activity at (14: 00-16: 00 and 22: 00-24: 00). The data presented in this investigation can be useful for the creation of management and conservation programs for the Reserve, its species and the interactions between them